Evaluation of Local Development Strategies and Process of Their Implementation in the Silesia Region - Adam Drobniak (European Regional Science Association (ERSA), 2003)
The paper is devoted to problems connected with adaptation of a strategic approach to the process of a local development planning by local authorities in the Silesia region. This approach have been popularised among the local governments in Poland in the second half of the 90's mainly due to the possibilities of utilisation of the EU pre-accession funds (e.g. PHARE). Hence the paper is an attempt of evaluation of the local development strategies utility in polish conditions under the experiences of the Silesian county towns. On the basis of the questionnaires and interviews' carried out among all the Silesian county towns and cities with the local authorities' representatives (mainly mayors and head of local government departments) - cross-evaluation was shown in the following aspects: methodology of local development strategy formulation; comprehension by local authorities the terms of development, strategies, goals, objectives; projects identification and defining; motivation which drives to take up the works on a strategy documentation; organisational changes connected with the strategy implementation process as well as real results and impacts of the strategies. In the field of the strategic planning methodology the degree of the advancement in using the strategy approach by local self-government was determined. Groups of county towns and cities with relatively great and small record of experience in using a strategy was distinguish. The research also was focused on the towns which have not a strategy, but their process of local development is visible with the naked eye. The above mentioned case studies enabled to do evaluation of the strategy approach usefulness in local development planning. It was also shown the participation of local communities, SMEs and other institution in a strategy formulation. Very interesting was the survey findings connected with the motivation of carry out the strategy formulation process and perceiving its desire effects. The general typology of motivation stimulus was shown. For example, it contains factors like: intentions to change a town image, desire to attract external investors, improving the local government effectiveness as well as imitation of behaviours of other towns and cities. The attention was also paid on the process of the strategic goals and objectives creation, their evaluation measures and identification of projects. The research confirmed a number of disagreements between objectives and projects and the lack of objectives measurement that, in practice enables to evaluate the advancement of their realisation. One of the key weaknesses of Silesian county towns strategies is the practice of defining the objectives in the large -extent that makes loss of concentration on serious local problems and ability to list almost unlimited number of projects, with a lack of hierarchy among them. Another aspect of the paper is focused on determination of using projects assessment methods by local governments in the financial, economical, environmental, social, technological, and risk aspects. The Silesia region experience proves a lack of system approach to project assessment and evaluation as well as problems with clear choice criteria determination.
Keywords: 330